INVESTIGATING ENGLISH STUDENTS IN WRITING RECOUNT TEXT USING PEER FEEDBACK THROUGH WEBLOG - Istiqomah Krisnadi (ISLLAC : Journal of Intensive Studies on Language, Literature, Art, and Culture, 2021)
This study aims to discover the response of English studentsin writing activity using peer feedback method through Google Classroomm in Singaperbangsa Karawang University. This study conducted with descriptive qualitative design to analyze students’ skill in writing activity especially writing recount text. The participants of this study are English students from four grades in Singaperbangsa Karawang University who had applied peer feedback and used Google Classroom in their writing class. In collecting the data, the researcher conducted an interview based on her interview guidelines and documentation to confirm the data. Using peer feedback through Google Classroom in writing activity has many benefits. The study found that the use of peer feedback through Google Classroom gives a positive impact for the students. It has improved their writing skills and increased their motivation to write more and better.